Winchester Diocese under John Stratford, 1323–1333 - Haines, Roy Martin (The journal of ecclesiastical history, 2013)
The intention of this article is to examine the principal features of John Stratford's Winchester episcopal register (Hampshire Record Office, 21M65/A1/5), recently edited for the Surrey Record Society, and hence to consider Stratford's reputation as a diocesan bishop insofar as this is determinable. Frequent absences on royal business, often abroad, are meticulously recorded, necessitating competent ‘central administration’ and a well-qualified and trusted familia. Both of these are in evidence. The impression given is of an efficiently run diocese with a surprising amount of pastoral work, particularly ordinations and visitation of monasteries, being performed by the bishop in person.